2016
DOI: 10.4306/pi.2016.13.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Sleep EEG Characteristics in Young and Elderly Patients with Obstructive Sleep Apnea Syndrome

Abstract: ObjectiveIn the present study, it was hypothesized that the sleep electroencephalogram (EEG) characteristics of young (<30 yrs) and elderly (>55 yrs) OSAS patients would differ.MethodsWe analyzed 76 sleep EEG recordings from OSAS patients (young group: n=40, mean age: 24.3±4.9 yrs; elderly group: n=36, mean age: 59.1±4.9 yrs), which were obtained during nocturnal polysomnography. The recordings were assessed via spectral analysis in the delta (0.5–4.5 Hz), theta (4.5–8 Hz), alpha (8–12 Hz), beta (12–32 Hz), sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For sleep spindles, these are considered as markers of N2 or nREM sleep microstructures (55,56). Previous studies have investigated this neurophysiologic phenomenon either only in N2 (22,37,40,57,58) or in both N2 and N3 stages (58). In the present study, we performed spindle analyses separately for N2 and N3.…”
Section: Discussionmentioning
confidence: 97%
“…For sleep spindles, these are considered as markers of N2 or nREM sleep microstructures (55,56). Previous studies have investigated this neurophysiologic phenomenon either only in N2 (22,37,40,57,58) or in both N2 and N3 stages (58). In the present study, we performed spindle analyses separately for N2 and N3.…”
Section: Discussionmentioning
confidence: 97%
“…SWA has also been shown to dissipate slower across the night in OSA relative to healthy individuals, suggesting disrupted sleep homeostasis from sleep fragmentation (Ondze et al, 2003). While no sex differences were noted for SWA in OSA, differences were found predictably across age groups with younger OSA patients having significantly higher relative SWA compared with elderly OSA patients (Lee et al, 2016; Munoz‐Torres et al, 2020). SWA in OSA also remained stable across time within individuals during an average time period of 3 months with no clinical or OSA severity changes (Poon et al, 2019).…”
Section: Eeg Measures Of Sleep Microstructure In Osamentioning
confidence: 98%
“…Spindle characteristics in OSA are also modulated by age. Lee et al showed that older OSA patients (> 55 years old) had higher activity in slow and fast sigma bands, reflecting slow and fast spindles, compared with younger OSA patients (< 30 years old), but no differences in slow‐to‐fast sigma ratio (representing proportion of slow versus fast spindles; Lee et al, 2016). AHI negatively correlated with slow‐to‐fast sigma ratio only in the younger group.…”
Section: Eeg Measures Of Sleep Microstructure In Osamentioning
confidence: 99%
“…Researchers have previously attempted to investigate the microstructure of PSG-derived sleep as well as waking quantitative EEG (qEEG) in BRSD [21][22][23][24][25]. The sigma (13− 15 Hz) power of sleep EEG predicted next-day sleepiness, as measured by the multiple sleep latency test [21].…”
Section: Introductionmentioning
confidence: 99%